Atmospheric Deposition of Nitrogen and Sulphur Compounds in the Czech Republic - Milos Zapletal (The Scientific World Journal)
Estimates of dry and wet deposition of nitrogen and sulphur compounds in the Czech Republic for the years 1994 and 1998 are presented. Deposition has been estimated from monitored and modeled concentrations in the atmosphere and in precipitation, where the most important acidifying compounds are sulphur diOxide, nitrogen Oxides, ammonia, and their reaction products. Measured atmospheric concentrations of SO2, NOx, NH3, and aerosol particles (SO42-, NO3–, and NH4+), along with measured concentrations of SO42-, NO3–, and NH4+ in precipitation, weighted by precipitation amounts, were interpolated with Kriging technique on a 10- x 10-km grid covering the whole Czech Republic. Wet deposition was derived from concentration values for SO42-, NO3–, and NH4+ in precipitation and from precipitation amounts. Dry deposition was derived from concentrations of gaseous components and aerosol in the air, and from their deposition velocities. A multiple resistance model was used for calculation of SO2, NOx, and NH3 deposition velocities. Deposition velocities of particles were parameterized. It was estimated that the annual average deposition of SOx in the Czech Republic decreased from 1384 to 1027 mol H+ ha-1 a-1 between 1994 and 1998. The annual average NOy deposition was estimated to be 972 and 919 mol H+-1 a-1 in 1994 and 1998, respectively. The annual average NHx deposition was estimated to be 887 mol H+-1 a-1 and 779 mol H+-1 a-1 in 1994 and 1998, respectively. It was estimated that the annual average of the total potential acid deposition decreased from 3243 to 2725 mol H+-1 a-1 between 1994 and 1998. Sulphur compounds (SOx) contributed about 38%, Oxidized nitrogen species (NOy) 34%, and reduced nitrogen species (NHx) 28% to the total potential acid deposition in 1998. The wet deposition contributed 42% to the total potential acid deposition in 1998.